Capitalist relations in Reality Settlement in BR-319 km 570 (Amazonas) - Neto, Thiago Oliveira (2017)
The production of food for the market aims to meet the consumption needs of urban centers, and, at the same time, family of the producer. Thus, the producer needs to establish relationships with the market, where the product or production surplus is sent; While another part remains in the very community where it is produced and where the producers live. The proceeds from the sale, as a rule, are used in the producer's own production. This brief general consideration is structured in the Incra settlement, located at kilometer 570 of the BR-319 highway, in the municipality of Humaitá, where agricultural producers organized to carry out production, processing and transportation to the consumer centers.